Differences in Hypertension and Stage II Hypertension by Demographic and Risk Factors, Obtained by Two Different Protocols in US Adults: National Health and Nutrition Examination Survey, 2017–2018. (25th March 2022) - Ostchega, Yechiam; Hughes, Jeffery P; Kit, Brian; Chen, Te-Ching; Nwankwo, Tatiana; Commodore-Mensah, Yvonne; Graber, Jessica E; Nguyen, Duong T
Abstract: BACKGROUND: To compare prevalence of hypertension and stage II hypertension assessed by 2 blood pressure (BP) observation protocols. METHODS: Participants aged 18 years and older ( n = 4, 689) in the National Health and Nutrition Examination Survey (NHANES 2017–2018) had their BP measured following 2 protocols: the legacy auscultation protocol (AP) and oscillometric protocol (OP). The order of protocols was randomly assigned. Prevalence estimates for hypertension (BP ≥130/80 mm Hg or use of medication for hypertension) and stage II hypertension (BP ≥140/90 mm Hg) were determined overall, by demographics, and by risk factors for each protocol. Ratios (OP% ÷ AP%) and kappa statistics were calculated. RESULTS: Age-adjusted hypertension prevalence was 44.5% (95% confidence interval [CI]: 41.1%–48.0%) using OP and 45.1% (95% CI: 41.5%–48.7%) using AP, prevalence ratio = 0.99 (95% CI = 0.94–1.04). Age-adjusted stage II hypertension prevalence was 15.8% (95% CI: 13.6%–18.2%) using AP and 17.1% (95% CI: 14.7%–19.7%) using OP, prevalence ratio = 0.92 (95% CI = 0.81–1.04). For both hypertension and stage II hypertension, the prevalence ratios by demographics and by risk factors all included unity in their 95% CI, except for stage II hypertension in adults 60+ years (ratio: 0.88 [95% CI: 0.78–0.98]). Kappa for agreement between protocols for hypertension and stage II hypertension was 0.75 (95% CI = 0.71–0.79) and 0.67 (95% CI = 0.61–0.72), respectively. CONCLUSIONS: In adults and for nearly all subcategories there were no significant differences in prevalence of hypertension and stage II hypertension between protocols, indicating that protocol change may not affect the national prevalence estimates of hypertension and stage II hypertension. Graphical Abstract: